Development and preliminary effectiveness of a smartphone‐based, just‐in‐time adaptive intervention for adults with alcohol misuse who are experiencing homelessness. (7th August 2022) - Walters, Scott T.; Mun, Eun‐Young; Tan, Zhengqi; Luningham, Justin M.; Hébert, Emily T.; Oliver, Jason A.; Businelle, Michael S.
Abstract: Background: Adults experiencing homelessness have much higher rates of alcohol misuse than housed individuals. This study describes the development and preliminary effectiveness of a smartphone‐based, just‐in‐time adaptive intervention (JITAI) to reduce alcohol use among adults experiencing homelessness. Methods: We conducted a pilot trial ( N  = 41; mean age [SD] = 45.2 [11.5]; 19.5% women) of the Smart‐T Alcohol JITAI where participants completed brief ecological momentary assessments (EMAs) each day, received personalized treatment messages following each EMA, and accessed on‐demand intervention content for 4 weeks. The prediction algorithm and treatment messages were developed based on an independent but similar sample as part of the trial. We examined three drinking outcomes: daily drinking (yes/no), drinks per day, and heavy episodic drinking, controlling for scores on the Alcohol Use Disorders Identification Test (AUDIT) at baseline, age, and sex using quadratic growth curve models. Results: Over the 4‐week period, participants showed a decline in all alcohol use outcomes. Participants also reported high levels of satisfaction with the JITAI. Conclusions: Use of the Smart‐T Alcohol JITAI was well received and provided encouraging evidence that it may reduce any drinking, drinks per day, and heavy episodic drinking among adults experiencing homelessness. Abstract : This study developed and tested the preliminary effectiveness of a smartphone‐based just‐in‐time adaptive intervention (JITAI) to reduce alcohol use among people experiencing homelessness. Using data from a sample of people who completed ecological momentary assessments (EMAs) over 4 weeks, we developed a prediction algorithm and corresponding treatment messages matched to momentary risk factors for alcohol use. In a second sample, people who received the tailored treatment messages reduced their drinks per day, any drinking, and heavy drinking over 4 weeks. The JITAI—Smart‐T Alcohol—shows promise as a treatment aid for people with alcohol misuse who are experiencing homelessness.